Biological impact of metal nanomaterials in relation to their physicochemical characteristics - Louro, Henriqueta (2020)
Corrigendum to "Biological impact of metal nanomaterials in relation to their physicochemical characteristics" [Toxicol in Vitro. 2019 Jan 29;56:172-183]. [Toxicol In Vitro. 2019]. Toxicol In Vitro. 2019 Feb 16. pii: S0887-2333(19)30110-9. doi: 10.1016/j.tiv.2019.02.001. [Epub ahead of print]. Disponível em: https://www.sciencedirect.com/science/article/pii/S0887233319301109?via%3Dihub